The optimization of semiconductor light, generating white light, heating regime - Dabulytė, Jurgita; Ivanauskas, Feliksas (Lietuvos matematikos rinkinys, 2023)
In this work the mathematical model of semiconductor light was employed. There were offered the distribution cases for monochromatic lighting sources.